2021
DOI: 10.2478/helm-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic effects of selected isoflavones on flatworms

Abstract: SummaryMedicinal plants have been successfully used in the ethno medicine for a wide range of diseases since ancient times. The research on natural products has allowed the discovery of biologically relevant compounds inspired by plant secondary metabolites, what contributed to the development of many chemotherapeutic drugs. Flavonoids represent a group of therapeutically very effective plant secondary metabolites and selected molecules were shown to exert also antiparasitic activity. This work summarizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…The antiparasitic activity of silymarin flavonolignans and some other flavonoids was recently reviewed by Faixová et al [159], demonstrating that some flavonoids and polyphenols can also be successfully used in parasitology-particularly on medically important flatworms such as Raillietina spp., Fasciola spp., Leishmania spp., Schistosoma spp., Echinococcus spp., and on the (model) cestode Mesocestoides vogae. Most of the existing papers worked with mixed preparations or with silymarin.…”
Section: Antiparasitic Activitymentioning
confidence: 99%
“…The antiparasitic activity of silymarin flavonolignans and some other flavonoids was recently reviewed by Faixová et al [159], demonstrating that some flavonoids and polyphenols can also be successfully used in parasitology-particularly on medically important flatworms such as Raillietina spp., Fasciola spp., Leishmania spp., Schistosoma spp., Echinococcus spp., and on the (model) cestode Mesocestoides vogae. Most of the existing papers worked with mixed preparations or with silymarin.…”
Section: Antiparasitic Activitymentioning
confidence: 99%
“…Unlike their vertebrate hosts and their free-living counterparts [ 153 ], these organisms depend exclusively on this enzyme to carry out the reduction of GSSG and Trx-S 2 . Although it has been proposed that having an enzyme capable of reducing substrates belonging to two independent redox systems represents an evolutionary advantage [ 148 ], it is also possible to note that the dependence of parasitic flatworms on this enzyme makes it an excellent pharmacological target [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ].…”
Section: Adaptations Of Parasitic Flatworms To Changes In Oxygen Tensionmentioning
confidence: 99%
“…We previously reported that the in vivo inhibition of the TGR in T. crassiceps cysticerci is sufficient to compromise the viability of the parasite by altering its redox state and glutathione metabolism [ 165 ], which agrees with observations made when incubating schistosomula in the presence of anti TGR iRNA [ 166 ]. Due to its importance, TGR has been crystallized [ 167 ], promoting the search for drugs capable of inhibiting it [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ].…”
Section: Adaptations Of Parasitic Flatworms To Changes In Oxygen Tensionmentioning
confidence: 99%
“…In parasitic diseases, flavonoids are a high interest group. This is due to their low toxicity in hosts and several mechanisms by which they can modulate pathologically altered processes during infections [6]. Flavonoids have multiple targets for treating leishmaniasis and include targets, such as arginase, ribonucleotide reductase and topoisomerase II [7,8].…”
Section: Introductionmentioning
confidence: 99%